SOURCES AND FORMATION CONDITIONS OF EARLY PROTEROZOIC GRANITOIDS FROM THE SOUTHWESTERN MARGIN OF THE SIBERIAN CRATON - Turkina O.M.; Nozhkin A.D.; Bayanova T.B. (My University, 2006)
Three stages of Early Proterozoic granitoid magmatism were distinguished in the southwestern margin of the Siberian craton: (1) syncollisional, including the formation of migmatites and granites in the border zone of the Tarak massif; (2) postorogenic, postcollisional, comprising numerous granitoid plutons of diverse composition; and (3) intraplate, corresponding to the development of potassic granitoids in the Podporog massif. Rocks of three petrological and geochemical types (S, I, and A) were found in the granitoid massifs. The S-type granites are characterized by the presence of aluminous minerals (garnet and cordierite), and their trace element distribution patterns and Nd isotopic parameters are similar to those of the country paragneisses and migmatites. Their formation was related to melting under varying H2O activity of aluminous and garnet-biotite gneisses at P < 5 kbar and T < 850°C with a variable degree of melt separation from the residual phases. The I-type tonalites and dioritoids show low relative iron content, high concentrations of CaO and Sr, fractionated REE distribution patterns with (La/Yb)n = 11-42, and variable depletion of heavy REE. Their parental melts were derived at T < 850°C and P > 10 and P < 10 kbar, respectively. According to isotopic data, their formation was related to melting of a Late Archean crustal (tonalite-diorite-gneiss) source with a contribution of juvenile material ranging from 25-55% (tonalites of the Podporog massif) to 50-70% (dioritoids of the Uda pluton). The most common A-type granitoids show high relative iron content; high concentration of high-field-strength elements, Th, and light and heavy REE; and a distinct negative Eu anomaly. Their primary melts were derived at low H2O activity and T ≥ 950°C. The Nd isotopic composition of the granitoids suggests contributions to the magma formation processes from ancient (Early and Late Archean) crustal (tonalite-diorite-gneiss) sources and a juvenile mantle material. The contribution of the latter increases from 0-35% in the granites of the Podporog and Tarak massifs to 40-50% for the rocks of the Uda and Shumikha plutons. The main factors responsible for the diversity of petrological and geochemical types of granitoids in collisional environments are the existence of various fertile sources in the section of the thickened crust of the collisional orogen, variations in magma generation conditions (αH2O, T, and P) during sequential stages of granite formation, and the varying fraction of juvenile mantle material in the source region of granitoid melts. © 2006 Nauka/Interperiodica.
Keywords: Proterozoic; Archean; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей; Precambrian::Archean